Prevalence of the Multi-drug Resistance of Shiga Toxin-producing Escherichia coli Isolated from Pigs in Central Thailand - Shutipen Buranasinsup (Science Faculty of Chiang Mai University, 2019)
Shiga toxin-producing E. coli (STEC), a strain producing cytotoxins known as Shiga toxins (Stxs, encoded by EVS and EVC genes), can cause neonatal and post-weaning diarrhea (PWD) in pigs, leading to substantial economic loss in the form of medication costs, reduced growth rate, and increased morbidity and mortality. To tackle this, several antimicrobial agents are used in pig farms, although misuse may lead to occurrence of antimicrobial-resistant pathogens. In this study, 5,831 E. coli bacterial isolates were collected from 715 pigs. Of these, 206 bacterial isolates were STEC carrying EVS–EVC genes. A majority of the STECs were resistant to ampicillin (99.5%), carbenicillin (99%), and trimethoprim/sulfamethoxazole (60.2%). Among these isolates, 93.69% and 0.97% of STEC were carried class 1 (6.8% belong to CS1) and class 2 integrons, respectively. None isolate carried CS2. The predominant antimicrobial resistance genes were blaTEM, aadA, sulII, dhfrV, and intI. The results of antimicrobial resistance phenotype and also genotype were correlated to antibiotics use in the swine farm such as amoxicillin and penicillin. Therefore, frequent use of antimicrobial drugs in pig farms may result in the occurrence of multi-drug resistant bacteria, and this should be taken into consideration prior to use.